2002
DOI: 10.1021/bi0204140
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Charge Preservation at Position 116 of αA-Crystallin Is Critical for Its Structural and Functional Integrity

Abstract: An autosomal dominant congenital cataract associated with a missense mutation, Arg-116 to Cys (R116C), in the coding sequence of human alphaA-crystallin has been reported. Subsequent study of this mutant, generated by site-directed mutagenesis, showed significant changes in secondary and tertiary structures, partial loss of chaperone activity, and substantially increased oligomeric size. The study presented here aims to show whether these changes are due to the loss of a positive charge at this position or due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 24 publications
7
51
2
Order By: Relevance
“…Consistent with this observation was a recent report (29) showing that mutation of R116C in ␣A-crystallin resulted in altered subunit composition with WT-␣B in the heteroaggregates and increased oligomer size compared with the oligomers of WT-␣A and WT-␣B subunits. Similarly, the mutation of Arg to Asp in ␣A-crystallin resulted in a drastic change in protein structure (30). This is consistent with Studer's study, which showed that chaperone activity is coupled to multimerization in bacterium ␣-HSP protein from Bradyrhizobium japonicum (31).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with this observation was a recent report (29) showing that mutation of R116C in ␣A-crystallin resulted in altered subunit composition with WT-␣B in the heteroaggregates and increased oligomer size compared with the oligomers of WT-␣A and WT-␣B subunits. Similarly, the mutation of Arg to Asp in ␣A-crystallin resulted in a drastic change in protein structure (30). This is consistent with Studer's study, which showed that chaperone activity is coupled to multimerization in bacterium ␣-HSP protein from Bradyrhizobium japonicum (31).…”
supporting
confidence: 88%
“…Using this method, the heteroaggregate formation between the following species at a ratio of 3:1 (␣A:␣B) was examined: (a) WT-␣A:WT-␣B; (b) ␣A-N101D mutant:WT-␣B; (c) ␣A-N123D:WT-␣B; (d) ␣A-N101D/N123D mutant:WT-␣B; (e) WT-␣A:␣B-N146D mutant. The purified WT-␣A/deamidated ␣A mutants were mixed with their purified counterparts in a 3:1 ratio (␣A:␣B), followed by denaturation in 4 M GdnHCl and renaturation as described by the Bera et al method (30). Briefly, the individual heteroaggregates were mixed to 4 M GdnHCl (final concentration) and incubated at 4°C for 6 h. This was followed by dialysis against 50 mM Tris-HCl, pH 7.9, at 5°C for 48 h with four changes of the buffer.…”
Section: Reconstitution Of ␣-Crystallin Heteroaggregatesmentioning
confidence: 99%
“…This could affect the tertiary and quaternary structure of proteins. For example, the loss of a single positive charge in ␣A-crystalline due to a mutation of arginine to cysteine results in significant change of the tertiary structure of this protein (27), significant diminishment of its chaperon-like activity, and has been suggested as a probable cause for development of congenital cataract (28). By taking into account that UVA can penetrate in the human lens (29) and that the latter contains high concentrations of ascorbate (30), we can expect that OP-lysine could play an important role in photochemical processes in the lens, based on the data for its photo-bleaching shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anti-oligomer antibody immunoreactivity can be present in native proteins, particularly HSPs. Missense mutations from arginine or lysine (a positive-charged amino acid), to glycine or cysteine can markedly alter protein structure, because it is known that a positive charge must be preserved at this position for the structural and functional integrity of small HSPs (26,27). Thus, higher immunoreactivity against an anti-oligomer antibody in mutant small HSPs may result from altered protein structure because of the loss of charge and changes in overall surface hydrophobicity of the protein (26).…”
Section: Discussionmentioning
confidence: 99%